2000
DOI: 10.1034/j.1399-0012.2000.140409.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Amphotericin B Lipid Complex Injection (ABLC) in solid‐organ transplant recipients with invasive fungal infections

Abstract: ABLC is safe and effective treatment for fungal infections in solid-organ transplant recipients. Its renal-sparing properties are particularly suited for this high-risk population for renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Our pooled analysis showed that fever occurred in one-third to one-half of patients receiving AmB, ABLC, and ABCD, which is consistent with previous reports [5,71]. On the basis of similar definitions, our findings regarding nephrotoxicity were also similar to findings in other analyses [5,8,71,72].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our pooled analysis showed that fever occurred in one-third to one-half of patients receiving AmB, ABLC, and ABCD, which is consistent with previous reports [5,71]. On the basis of similar definitions, our findings regarding nephrotoxicity were also similar to findings in other analyses [5,8,71,72].…”
Section: Discussionsupporting
confidence: 82%
“…Although available commercially outside of the USA for several years, a third product, liposomal AmB, or LAmB (AmBisome; NeXstar Pharmaceuticals/Fujisawa, San Dimas, CA, USA), received FDA approval in 1997. A majority of patients receiving these newer formulations have demonstrated intolerance to AmB or are documented to have Aspergillus infections refractory to AmB conventional therapy [3,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many experts choose lipid amphotericin B for patients with underlying kidney disease and for those at increased risk of developing nephrotoxicity. However, support for its use in blastomycosis comes from animal models and anecdotal clinical experience (27,29,31,34,75,93,99).…”
Section: Treatment Treatment Optionsmentioning
confidence: 99%
“…VC and CAS showed very high MIC 90 s, 8 to 16 g/ml and 128 to Ͼ256 g/ml, respectively. AMB has traditionally been the treatment of choice for zygomycosis (1,2,4,12,18,24). The limited clinical use of ITC in the treatment of zygomycosis does not allow us to draw any conclusions from the in vitro data (8,15,17).…”
mentioning
confidence: 99%